Percevoir la marche en ville avec un oculomètre (eye tracker) - Spyros Franguiadakis; Thierry Boissière; Mouloud Boukala; Denis Cerclet (Revue d'anthropologie des connaissances)
Based on a device for capturing urban walking using an eye tracker, this article describes the process of emergence of an embodied ethnographic method for accessing and analyzing the actions of others in the process of being performed. This processual, plural and “integrative” ethnographic approach - in which participants are invited to analyze their own actions - studies urban travel through first-person analysis. This approach demonstrates the close relationship between the ethnographic survey device and the analytical device. A sensitive and empathetic relationship with the survey material (video recordings of captures, explanation and self-confrontation interviews), where learning to perceive others and their actions takes precedence, offers the opportunity to move from an exteriority to observational data to their "embodied" apprehension. The aim is to get as close as possible to the action in progress, and to understand what it involves and means for the individual.